Bioactivity Evaluation of Hydroxyapatite–Salacca Zalacca Peel Extract–Collagen Formulation for Dental Pulp Regeneration Material: In Vitro Study - Heidi Edwina Halim; Elline; Melaniwati; Eddy (FKG Universitas Syiah Kuala, 2026)
Regenerative endodontic therapy can restore the pulp–dentin complex through the use of biocompatible materials that promote cell viability and migration. Salacca zalacca peel extract contains polyphenols and antioxidants with potential that to enhance cellular activity. Hydroxyapatite (HAP) exhibits biomimetic properties similar to dentin mineral, and collagen (COL) supports cell adhesion, proliferation, and structural integrity. This study aimed to investigate the cytocompatibility and migratory response of hDPSCs toward HAP–SAL–COL formulations with varying SAL concentrations as potential materials for regenerative endodontic applications. An experimental post-test-only control group design was performed using 4% HAP synthesized from eggshells combined with SAL extract at 5%, 10%, and 15%, along with collagen. Cytotoxicity was determined at 24 hours using the MTT assay, while cell migration was evaluated for 24 hours by scratch assay. Cell viability ranged from 107% to 115%, indicating non-cytotoxicity and enhanced metabolic activity. The HAP + SAL 5% + COL group demonstrated highest migration rate (24.96 ± 4.00%), significantly than control group (p<0.05). In conclusion, the HAP+SAL5%+COL formulation exhibits good biocompatibility, suggesting its potential as bioactive material for regenerative endodontic therapy in vital pulp treatment.